Reflection on Social Cohesion of Sasak Speakers and the Trends Transformed - Saharudin, Saharudin (UI Scholars Hub, 2014)
This article presents the social cohesiveness of traditional Sasak reflected and expressed in their linguistics, particularly at social capital domain, and to transform it to the current social capital of Sasak people. The category and linguistic expressions are considered to be the lingual category forms and the verbal expressions in the social capital domain, in which it is kept various knowledge systems of the social cohesiveness of Sasak people. Transformation in this study is defined as a shift at the surface structure (the lingual transformation) and deep structure (the behaviour transformation) of Sasak people, it is used the ethnosemantic approach, by investigating certain vocabularies in the language they use in the social domain having relationship with the social capital. This study reveals three social capitals of Sasak people becoming the base of values: (1) the social capital referring to the interactional forms, (2) to the institutional forms, and (3) to the norms. Furthermore, the social transformation tendency is caused by (i) the new qualification needs, (ii) the shift of professional role, and (iii) the existence of the complexity stratification, and (iv) the existence of new various institutions formed by the governments and the formal system power.